Household Debt: Is It a Liability? - Williams, R (My University, 2009)
The factors contributing to the increase in household debt in Australia are discussed in some detail in the Forum articles. The role of the deregulation of the financial sector is examined in the article by Green, Harper and Smirl. They emphasise the effects of greater competition in the lending market, which both lowered the costs of borrowing and broadened the range of products. Households benefited through an increase in net wealth and greater freedom to allocate consumption through time. The article by Bloxham and Kent also includes an examination of the causes of the build-up of household debt, comparing the Australian experience with that of other Organisation for Economic Co-operation and Development countries. Their list of causal factors includes deregulation, low levels of inflation and unemployment, reductions in borrowing costs and reduced macroeconomic volatility, but they comment that it is difficult to ascribe precise degrees of significance to each factor. In his article, Keen asserts that the responsibility for the build-up of debt ‘lies not with the irrational exuberance of borrowers, but with the credit-creation practices of lenders’.
Keywords: Income & Finance -- Debt; Income, wealth and finances; Income & Finance; Debt; Income, wealth and finances